Classifications of Controlled Substances: Insights from 23 Countries - Lisa Dragic; Elease Lee; Albert Wertheimer (University of Minnesota Libraries Publishing, 2015)
Controlled substances are among the most highly regulated and highly abused medications. The purpose of this study was to describe the classification systems for controlled substances in 23 countries and make comparisons. From this review, recommendations are provided for improving classification systems and their impact on medication use.   Type: Student Project